2020
DOI: 10.3389/fcell.2020.595637
|View full text |Cite
|
Sign up to set email alerts
|

miR-429-3p/LPIN1 Axis Promotes Chicken Abdominal Fat Deposition via PPARγ Pathway

Abstract: To explore the regulatory mechanism of abdominal fat deposition in broilers, 100-day-old Sanhuang chickens (n = 12) were divided into high-fat and low-fat groups, according to the abdominal fat ratio size. Total RNA isolated from the 12 abdominal fat tissues was used for miRNA and mRNA sequencing. Results of miRNA and mRNA sequencing revealed that miR-429-3p was highly expressed in high-fat chicken whereas LPIN1 expression was downregulated. Further, we determined that miR-429-3p promoted preadipocyte prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…This is probably because the beneficial effects of B. subtilis in broilers were markedly strain-dependent ( 7 , 32 ). Abdominal fat is an important index used to measure lipid deposition in broilers ( 33 , 34 ). Excessive fat deposition is undesirable, because it degrades meat quality, decreases feed efficiency, and increases production and health costs ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is probably because the beneficial effects of B. subtilis in broilers were markedly strain-dependent ( 7 , 32 ). Abdominal fat is an important index used to measure lipid deposition in broilers ( 33 , 34 ). Excessive fat deposition is undesirable, because it degrades meat quality, decreases feed efficiency, and increases production and health costs ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…An accumulation of abdominal fat in chickens is correlated with changes in diet and causes great economic loss to the chicken industry. In our previous study [ 15 ], transcriptome sequencing was performed for high and low abdominal fat rates in 100-day-old Sanhuang broilers (accession ID: PRJNA656618), and we found that PROS1 was aberrantly upregulated in the abdominal fat tissues of the low-abdominal fat broilers ( Figure 1 A). qPCR validation was performed to confirm the difference in mRNA expression of PROS1 in broilers’ abdominal fat between a high abdominal fat ratio and a low abdominal fat ratio ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 92%
“…In fact, the most obvious feature of PROS1 is its TAM receptor-independent anticoagulation [ 17 , 18 ]. In our previous study, PRSO1 was upregulated in abdominal fat tissues from the individuals with low-abdominal fat rates [ 15 ], implying its potential role in chicken lipid metabolism. However, no studies on chicken PROS1 have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal fat accounts for 22% of body fat, but is generally considered waste, due to its low economic value [ 1 ]. Excessive deposition of abdominal fat in broilers not only results in low feed conversion rate, fertility, and semen quality, but also affects the economy of the industry [ 2 , 3 , 4 ]. Currently, decreasing abdominal fat deposition is one of the objectives of broiler production.…”
Section: Introductionmentioning
confidence: 99%